The status of Cola germplasm and its conservation in Nigeria - Adebola, P.O.=700 1 Badaru, K.
(En, Fr, Es)
ilus., 8 ref.
Keywords: COLA; NUEZ DE COLA; CONSERVACION DEL GERMOPLASMA; NIGERIA; COLA NITIDA; COLA ACUMINATA